STUDIES ON THE MORTALITY IN SPAWN AND FRY OF INDIAN MAJOR CARPS DURING TRANSPORT - Saha, K C; Chaudhury, N K (Indian Journal of Fisheries, 2015)
During transport of carp spawn (dimpom), the use of a specific red soil and water medium is a. common practice in West Bengal from time immemorial. As the entire spawn trade is in the hands of indigenous spawn dealers, the reason for the use of such a specific soil in the medium of transport, has not hitherto been scientifically explored.